Implementasi Model Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPA - Sholichah, Ana; Dyah Kusumawati, Putri Rahadian (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The use of the right model in the teaching and learning process will create an active learning atmosphere, not only focused on teacher activities, but also on student activities. Teachers are expected to be able to carry out their duties and functions as teachers and be able to apply models that are in accordance with the material so that they can improve student learning outcomes. This study describes the activities of teachersin the implementation of problem based learning models in improving student learning outcomes in science learning, student activities during the implementation of problem based learning models, and student learning outcomes in science learning by implementing problem based learning models. This study uses classroom action research using quantitative descriptive analysis. Based on the results of the research data analysis, it was found that the implementation of the problem based learning model in improving student learning outcomes in science learning.